Medical toxicology - Murray, Brian Patrick; Carpenter, Joseph (Joseph Edward) (New York, NY : Oxford University Press, 2023)
'Medical Toxicology' is an interactive, case-based book that covers content not found in most general specialty textbooks, and gives readers the opportunity to prepare for board certification and recertification, and to gain medical toxicology expertise without the need to perform a deep dive into the literature. The chapters go beyond the basics of common and dangerous toxicities and provide the next step of care for complicated cases, as well as backgrounds to the pathophysiology of severe overdoses. It also addresses multiple overdoses, poisonings, and envenomations and supplements the information and recommendations of a poison centre or toxicologist by providing background reasoning when a deep dive into a particular topic is not possible.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on December 13, 2023).
Keywords: Clinical toxicology; Emergency medicine; Health and Wellbeing; Clinical & internal medicine